2020
DOI: 10.1002/ange.202012469
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Low Loading Pt/CeO2 Catalysts: Ceria Facet Effect Affords Improved Pairwise Selectivity for Parahydrogen Enhanced NMR Spectroscopy

Abstract: Oxide supports with well‐defined shapes enable investigations on the effects of surface structure on metal–support interactions and correlations to catalytic activity and selectivity. Here, a modified atomic layer deposition technique was developed to achieve ultra‐low loadings (8–16 ppm) of Pt on shaped ceria nanocrystals. Using octahedra and cubes, which expose exclusively (111) and (100) surfaces, respectively, the effect of CeO2 surface facet on Pt‐CeO2 interactions under reducing conditions was revealed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Therefore, new synthesis approaches are expected to be developed to enhance the amount of surface active oxygen species on the SAC. (4) Solid catalysts exposing different crystal planes have been reported to present different catalytic performances, [32h] whereas metal single atoms supported on the different planes of a faceted oxide have different coordination environments, exhibiting different catalytic properties, as was recently reported for a Pt 1 /CeO 2 SAC [57] . Therefore, further studies are suggested to investigate metal SACs supported on reducible supports exposing different planes, especially for low‐temperature oxidation of VOCs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Therefore, new synthesis approaches are expected to be developed to enhance the amount of surface active oxygen species on the SAC. (4) Solid catalysts exposing different crystal planes have been reported to present different catalytic performances, [32h] whereas metal single atoms supported on the different planes of a faceted oxide have different coordination environments, exhibiting different catalytic properties, as was recently reported for a Pt 1 /CeO 2 SAC [57] . Therefore, further studies are suggested to investigate metal SACs supported on reducible supports exposing different planes, especially for low‐temperature oxidation of VOCs.…”
Section: Discussionmentioning
confidence: 95%
“…(4) Solid catalysts exposing different crystal planes have been reported to present different catalytic performances, [32h] whereas metal single atoms supported on the different planes of a faceted oxide have different coordination environments, exhibiting different catalytic properties, as was recently reported for a Pt 1 /CeO 2 SAC. [57] Therefore, further studies are suggested to investigate metal SACs supported on reducible supports exposing different planes, especially for lowtemperature oxidation of VOCs. (5) When testing catalyst performances in VOCs oxidation, most studies have focused on the oxidation of a VOC molecule.…”
Section: Discussionmentioning
confidence: 99%